Implementation of the Traditional Game 'Ular Naga' for Locomotor Movement of 4-5 Year Old Children - Afifah, Mar'atul; Prabowo, Trisnar Adi; Indarto, Asyidika Vito; Febriansyah, Adhi Yunus; Arrosyid, Abdulloh Azzam (Jurnal Pendidikan Jasmani (JPJ), 2025)
The purpose of this study was to examine of implementation the traditional game of the ‘ular naga’ in improving the locomotor movement of kindergarten children aged 4-5 years. This type of research is a quasi-experimental with pretest-posttest. Then the sample consisted of 64 children aged 4-5 years from kindergartens in Paguyangan District, Brebes, Indonesia. There are 32 children who receive treatment using the traditional game 'ular naga' or the experimental group (EG) and 32 children with games that are played freely or the control group (CG). The intervention was carried out for 8 weeks with 2 meetings each week, on Tuesday and Friday, starting at 07.30 - 09.00. Locomotor movement assessment using a validated rubik (table 1). The results of the t-test are EG and CG have an effect on locomotor movement (EG = sig. 0,000 and CG = sig. 0,037). However, the independent t-test showed sig. 0.000 which means that the experimental group (EG) using the traditional 'ular naga' game is recommended to improve locomotor skills in kindergarten children aged 4-5 years. Future research can explore the influence of other traditional games, utilize technology to measure motor development in more detail, and expand the duration of observation to see long-term effects.